Making sense of managing culture - Cray, David, 1946-; Mallory, Geoffrey R. (London : International Thomson Business Press, 1998)
This book is about: A larger and smaller world; Traditional approaches to comparative research; Strategy and culture; Culture and cognition; People and culture; A cognitive approach to international management.
Keywords: Management; Organization; Organizational behavior; Intercultural communication; Industrial sociology; International business enterprises -- Management; Comparative management; Industrial management -- Cross-cultural studies; Corporate culture